An experimental study on the behaviour of glass filled polypropylene and polyethylene composite pipes under quasi-static axial loading - Ya, H.H. (Penerbit UTM Press, 2015)
The behaviour of extruded glass fibre reinforced thermoplastic pipes under axial crushing load was investigated experimentally. It was envisaged that the difference between the axial and hoop moduli and strengths as well as the volume fraction would influence the mode of collapses and energy absorption. The moduli could be varied using a new extrusion technology, which controls the fibre orientation pattern, hence, the mechanical properties. The ability to vary the moduli and the fibre volume fraction provides means of controlling the collapse mode in order to optimize specific energy absorption. Axial compression tests were performed on glass filled Polypropylene (GPP) and glass filled Polyethylene (GPE) composite pipes. The samples were chosen with a variety of fibre volume fraction (Vf = 5 to 20 and average angle of orientation θ= 50o to 80o) to evaluate the effect of anisotropy and Vf to the collapse modes when subjected to axial static loading. The results from the experiments revealed that typical axial and hoop modulus (Ea and Eθ ) of GPP and GPE pipes increased with increasing of θ from 55º to 75º and decreased gradually in between 75º to 80º. The axial modulus was increased constantly with the increase of Vf from 5 to 20 . However, the hoop modulus is the highest at 5 Vf, decreases significantly at 10, and gradually increases at 20. It is noticed that, the GPP and GPE pipes contain higher Vf and θ, collapsed in brittle failure mode (fragmentation), whereas those with less Vf and θ angle, collapsed in non-axis-symmetric (diamond) mode with the local fracture while the local fracture disappeared with lower fibre contents. © 2015 Penerbit UTM Press. All rights reserved.